Impact of a judicial system reform on police behavior : evidence on juvenile crime in Colombia (2017)
This paper uses a natural experiment to identify the impact of a judicial system reform on police behavior. The study finds that, after a decrease in the severity of judicial punishment imposed on Colombian adolescents, arrest rates for adolescents in most misdemeanor crimes decreased due to a change in police behavior. The magnitude of this effect ranged between 0.08 to 0.321 standard deviations. The uncertainty on how to operate the new system, the lack of training, and the potential disciplinary sanctions led police officials to reduce arrest rates. Nonetheless, police forces learned gradually how to operate within the new system and adjusted their operations, countervailing the initial negative impact on arrest rates. We present suggestive evidence that the reduction in arrest rates and the lower sanctions increased crime incidents in cities with a large proportion of adolescents in their population. Qualitative evidence collected in focus groups with police officials supports the principal quantitative findings and contextualize the obstacles that led to the decrease in arrest rates and the perceived increase of juvenile crime based on the officials' experiences in the streets.